The Role of Generative AI and Digital Transformation in Modernizing Performance Management Processes: Goal Setting - Rishi Venkat; Darshana Suresh; Prakhar Mittal; Manoj Lakhamraju; Kiran Babu Macha (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Artificial Intelligence and digital transformation have revolutionized traditional business operations, resulting in enhanced performance management systems. Performance management systems are frequently perceived as fundamental compliance initiatives. However, the efficacy of a performance management system can significantly contribute to human resource capital investment and cost reduction. It is important to invest in an effective performance management system that can enable continuous monitoring of employee engagement and attrition risk. This study aims to provide an analysis of how Artificial Intelligence (AI) and AI-based products can drive efficiency within the performance management process. Performance management systems can improve transparency, reduce bias and provide insights for managers leading to improved decision-making. The necessity to replace legacy systems with contemporary AI-driven performance management systems benefits organizations both operationally and strategically.